BIODEGRADABLE FOAM BASED ON COCOA SHELL AND DURIAN SEED STARCH WITH DEGRADATION AGENT FROM ORANGE PEEL - Akbil Fikran; Azmil Pratama Nugraha; Mutassim Billah (Fakultas Teknik Universitas Wahid Hasyim, 2024)
AbstractCocoa shell waste has the potential to be used as the main filler for biodegradable foam because it has a high cellulose fiber content of around 44.08%. This fiber will become a reinforcement of the main ingredient of biofoam, namely durian seed starch which has a starch content of around 26.607%. Limonene compounds contained in citrus fruits also show activity as a degradation agent in Styrofoam material. This study aims to determine the effect of cocoa peel and orange peel on water absorption, biodegradation and tensile strength of the formed biofoam. The process of making biofam consists of mixing the ingredients for each variable, printing and pressing. The variables used are the mass composition of cocoa peel 25%, 20%, 15%, 10%, 5% and the mass composition of orange peel 0%, 5%, 10%, 15%, 20%. Based on the results of this study, it was obtained that biofoam for a concentration of 15% cocoa shell was included in the standard biodegradable foam, a concentration of 20% orange peel powder was included in the standard biodegradable foam because it was completely degraded (100%) for 6 months or 180 days and the tensile strength value of biofoam from all concentrations in this study was still not in accordance with the Indonesian National Standard (SNI).Keywords: biofoam; cocoa fiber shells; Starch; limonene compounds